Akses dalam Perdagangan Lada Kesultanan Banten di Lampung: Analisis terhadap Dalung Bojong - Muhamad Alnoza (Tsaqofah, 2022)
This research was conducted by focusing on the profit-sharing system of the pepper merchantilisim during the Banten Sultanate in Lampung, with the coverage of the Dalung Bojong case study. Dalung Bojong is an inscription made of copper issued by Sultan Abu Al-Mahasin of Banten (1690-1733 AD), whose contents are related to the regulation of the delivery of pepper from Lampung to Banten. This research specifically raises the issue of how the process of distributing profits from the pepper production of the Sultanate of Banten? The purpose of this research is to map the flow of profits from pepper using access theory. Both of them benefit equally, where the people of Lampung are the producers and the Sultanate of Banten is the distributor.